Identification of a new cannabidiol n-hexyl homolog in a medicinal cannabis variety with an antinociceptive activity in mice: cannabidihexol - Pasquale Linciano (Nature Portfolio, 2020)
Abstract The two most important and studied phytocannabinoids present in Cannabis sativa L. are undoubtedly cannabidiol (CBD), a non-psychotropic compound, but with other pharmacological properties, and Δ9-tetrahydrocannabinol (Δ9-THC), which instead possesses psychotropic activity and is responsible for the recreative use of hemp. Recently, the homolog series of both CBDs and THCs has been expanded by the isolation in a medicinal cannabis variety of four new phytocannabinoids possessing on the resorcinyl moiety a butyl-(in CBDB and Δ9-THCB) and a heptyl-(in CBDP and Δ9-THCP) aliphatic chain. In this work we report a new series of phytocannabinoids that fills the gap between the pentyl and heptyl homologs of CBD and Δ9-THC, bearing a n-hexyl side chain on the resorcinyl moiety that we named cannabidihexol (CBDH) and Δ9-tetrahydrocannabihexol (Δ9-THCH), respectively. However, some cannabinoids with the same molecular formula and molecular weight of CBDH and Δ9-THCH have been already identified and reported as monomethyl ether derivatives of the canonical phytocannabinoids, namely cannabigerol monomethyl ether (CBGM), cannabidiol monomethyl ether (CBDM) and Δ9-tetrahydrocannabinol monomethyl ether (Δ9-THCM). The unambiguously identification in cannabis extract of the n-hexyl homologues of CBD and Δ9-THC different from the corresponding methylated isomers (CBDM, CBGM and Δ9-THCM) was achieved by comparison of the retention time, molecular ion, and fragmentation spectra with those of the authentic standards obtained via stereoselective synthesis, and a semi-quantification of these cannabinoids in the FM2 medical cannabis variety was provided. Conversely, no trace of Δ9-THCM was detected. Moreover, CBDH was isolated by semipreparative HPLC and its identity was confirmed by comparison with the spectroscopic data of the corresponding synthetic standard. Thus, the proper recognition of CBDH, CBDM and Δ9-THCH closes the loop and might serve in the future for researchers to distinguish between these phytocannabinoids isomers that show a very similar analytical behaviour. Lastly, CBDH was assessed for biological tests in vivo showing interesting analgesic activity at low doses in mice.